Fast pyrolysis of oil palm kernel shell in a fluidized bed reactor: The effect of biomass size on the yields of pyrolysis products - Uemura, Y. (Trans Tech Publications Ltd, 2014)
This study investigates the effect of biomass size on the yields of char, liquid (organic compounds and water) and gas for fast pyrolysis of palm kernel shell (PKS). Fast pyrolysis was carried out in a fluidized bed reactor of 108 mm in internal diameter operated at 450 â using three different sizes of palm kernel shell (0.325, 0.75 and 1.5 mm). In specific the effect of biomass size on the yields of known and unknown organics in bio-oil was mainly investigated. The major organics include acetic acid, phenol and furfural. The minor ones include 2-methylphenol, 4-methylphenol, 2-methylnaphthalene, benzene, toluene and tetrahydrofurane (THF). Smaller biomass sizes were favorable for higher bio-oil yields. Â© 2014 Trans Tech Publications, Switzerland.